VD_FINDINFO HC / 2014 / 323 vom 22. August 2014 - VD Tribunal cantonal (2014)
INTERPRÉTATIONSENS GÉNÉRAL, ASSURANCE PRIVÉE, CONTRAT D'ASSURANCE, DEGRÉ DE L'INVALIDITÉ, INVALIDITÉINFIRMITÉ, NOTION | 18 al. 1 CO, 46 LCA, 88 LCA